2021
DOI: 10.3390/cells10061410
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory miRNA–mRNA Networks in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second-most common neurodegenerative disease, and its pathophysiology is associated with alpha-synuclein accumulation, oxidative stress, mitochondrial dysfunction, and neuroinflammation. MicroRNAs are small non-coding RNAs that regulate gene expression, and many previous studies have described their dysregulation in plasma, CSF, and in the brain of patients with PD. In this study, we aimed to provide a regulatory network analysis on differentially expressed miRNAs in the brain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…The majority of these genes encode proteins that are linked either directly or indirectly to quality control mechanisms that are vital in maintaining cell homeostasis, vesicular transport pathways, autophagy processes, and the endo-lysosomal system. Other genetic alterations have also been associated with PD, including epigenetic changes, such as DNA methylation, chromatin remodeling, histone modifications, microRNAs and long non-coding RNAs [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these genes encode proteins that are linked either directly or indirectly to quality control mechanisms that are vital in maintaining cell homeostasis, vesicular transport pathways, autophagy processes, and the endo-lysosomal system. Other genetic alterations have also been associated with PD, including epigenetic changes, such as DNA methylation, chromatin remodeling, histone modifications, microRNAs and long non-coding RNAs [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous study [ 42 ] showed that there is downregulation of Dicer expression in dopamine neurons of aged mice, accompanied by general decrease in miRNAs expression. There are also data demonstrating reduced Dicer levels in dopamine neurons of PD patients [ 43 , 44 ], as well as alterations in regulatory miRNA-mRNA networks in PD [ 45 ]. Abnormalities in miRNA networks were also reported in the context of various pathological conditions outside of CNS, such as in pancreas and liver (reviewed [ 14 , 15 ], respectively).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it should be noted that the reported characteristics of individuals in these studies were extremely insufficient -for example, none of the articles provided information on the stage and clinical form of PD [73,82,83]. A total of 99 miRNAs differentially expressed in the substantia nigra in PD have been identified to date, with 60 miRNAs being upregulated and 39 miRNAs -downregulated [84]. These studies have shown that the miRNA sets expressed in the brain in PD change significantly, and such changes can cause certain abnormalities in the expression of genes involved in the metabolic pathways associated with the PD pathogenesis.…”
Section: Epigenetic Factors In the Development Of Parkinson's Diseasementioning
confidence: 99%
“…Thus, expression of parkin gene is regulated by at least four miRNAs (miR-103a-3p, miR-146a, miR-181a, miR-218), dardarin gene -two miRNAs (miR-205, miR-599), and DJ-1 gene -two miRNAs (miR-494, miR-4639). As a result, miRNAs are involved in the regulation (both positive and negative) of a large number of metabolic processes associated with the PD development, such as mitochondrial dysfunction and oxidative stress, autophagy, apoptosis, inflammation, and neurotrophin expression [84,85].…”
Section: Epigenetic Factors In the Development Of Parkinson's Diseasementioning
confidence: 99%